Phylogenetic Study of Mangifera laurina and its Related Species Using cpDNA trnL-F Spacer Markers - . Fitmawati; Alex Hartana (HAYATI Journal of Biosciences, 2010)
Phylogenetic study of cpDNA intergenic spacer trnL-F of Mangifera laurina and their related species within the genus Mangifera in Indonesia was conducted using Rutaceae as the outgroup. This study was to reconstruct phylogenetic relationships and to understand infraspecific relationships within Mangifera based on cpDNA trnL-F intergenic spacer sequences. The results showed that Mangifera sp. Hiku (mangga hiku) as the basic cultivar in the clade, and it supported the monophyletic group in Mangifera. And phylogenetic construction indicated that Mangifera sp. Hiku was the progenitor of M. laurina and their related species.